Spectroscopic and Morphological Studies of Metal-Organic and Metal-Free Dyes onto Titania Films for Dye-Sensitized Solar Cells. (5th October 2013) - Di Carlo, Gabriella; Caschera, Daniela; Toro, Roberta G.; Riccucci, Cristina; Ingo, Gabriel M.; Padeletti, Giuseppina; De Marco, Luisa; Gigli, Giuseppe; Pennesi, Giovanna; Zanotti, Gloria; Paoletti, Anna M.; Angelini, Nicola
Abstract : We have investigated the spectroscopic behavior of three different sensitizers adsorbed onto titania thin films in order to gain information both on the electron transfer process from dye to titania and on the anchorage of the chromophore onto the semiconductor. We have examined by UV-Vis and fluorescence spectroscopy the widely used ruthenium complex cis -di(thiocyanato)bis(2, 2′-bipyridyl-4, 4′-dicarboxylato)ruthenium(II) (N719), the more recently developed organic molecular 3-(5-(4-(diphenylamino)styryl)thiophen-2-yl)-2-cyanoacrylic acid (D5), and a push-pull zinc phthalocyanine sensitizer (ZnPc). Three type of titania films with different morphology, characterized by SEM and FT-IR measurement, were considered: a mesoporous transparent film deposited by spin-coating (TiMS), a semiopaque film deposited by doctor-blade from mesoporous titania (TiMS_DB) and a semiopaque film deposited by doctor-blade form commercial P25 titania (P25_DB). The use of TiMS is responsible for the adsorption of a higher amount of dye since the mesoporous structure allows increasing the interfacial area between dye and titania. Moreover, the fluorescence emission peak is weaker when the sensitizers are adsorbed onto TiMS. These findings suggest that mesostructured films could be considered the most promising substrates to realize photoanodes with a fast electron transfer process.